(untitled) (Global Journal of Medical Research, 2021)
There are five sense organs (Panch Gyanendriya) mentioned in Ayurvedic Samhitas i.e. eye(chakshu), ear(shrota), nose(ghrana), tongue(rasana) and skin(twak). One of these is eye (Drishti) which is most important sense organ in our body. Acharya Sushruta the eminent Ayurveda region, has described the Drishti very accurately in his treatise Sushruta Samhita. There are six Netra Patala told in Ayurvedic classics which can be anatomically correlated with different layers of eyes as explained in modern ophthalmology. Drishti is a controversial word in Shalakya Tantra, a lot of meanings of Drishti have been taken in the Sushruta Samhita 1 . So Drishti can be simply considered as the functional unit of eye, which performs vision. It is not mere an anatomical structure but the composition of all the essential dhatus of internal eye ball.In ancient Ayurvedic scriptures have explained Netra Rachna Sharir and Kriya Sharir in a beautiful descriptive manner, still there is need of exploring the terminologies for proper understanding of pathogenesis of Netra Rogas and their managements so that implementation of Ayurvedic concepts can be done in eradication of Drishtigata Rogas in a fruitful manner to serve the humanity.